Sludge carbon adsorption material and preparation method thereof

By filling porous network particles inside the sludge and adopting ZrV2O7 coating technology, the pore structure and adsorption capacity of the sludge are improved, and the problem of limited adsorption capacity of the existing sludge activated carbon is solved, achieving more efficient removal of pollutants in water.

CN119897062APending Publication Date: 2025-04-29SUZHOU ZHONGSHENG ENVIRONMENTAL REMEDIATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550662.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The pore structure of existing sludge activated carbon is poor and has limited adsorption capacity, making it difficult to meet the demand for efficient removal of heavy metals and organic pollutants in water.

Method used

The porous network particles are filled inside the sludge, and ZrV2O7 is used to coat the porous network particles to form a C-ZrV2O7 structure, improving the stability and specific surface area of ​​the porous structure.

Benefits of technology

Through improved porous structure and cladding materials, the adsorption rate and stability of sewage peat are significantly improved, and the removal capacity of heavy metals and organic pollutants is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897062A_ABST
    Figure CN119897062A_ABST
Patent Text Reader

Abstract

The invention provides a sludge carbon adsorption material and a preparation method thereof. Porous network particles are arranged in the sludge carbon adsorption material and are spherical, the particle size of the porous network particles is 0.5-5 microns, the pore diameter of the porous network particles is 2-23 nm, and the porosity of the porous network particles is 80-97%. According to the invention, the porous network particles are filled in the sludge carbon to form a regular porous structure; the porous network particles have a very large specific surface area, so that the overall specific surface area of the sludge carbon can be increased, and the adsorption rate is improved; zrV2O7 is adopted to coat the porous network particles, and ZrV2O7 is a negative thermal expansion material, is expanded after being cooled in the preparation of the internal porous structure of the sludge carbon, can be more tightly filled in the sludge carbon, and can be further combined with the sludge carbon to construct a C-ZrV2O7 structure and improve the stability of the internal porous structure of the sludge carbon; meanwhile, after grinding, the coating rate of ZrV2O7 is about 80%, a porous structure is further formed on the surface of the porous net film, and the specific surface area is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a sludge carbon adsorption material and a preparation method thereof. Background Art

[0002] With the development of industry and the overexploitation of available resources, a large amount of heavy metal elements have entered the water body. Heavy metal elements such as arsenic, cadmium, lead, mercury, and chromium are highly toxic, non-biodegradable, persistent, and bioaccumulative, causing great harm to my country's ecological environment and human health. The removal methods of heavy metals include adsorption, chemical precipitation, electrochemical method, ion exchange, membrane separation, etc. Among them, adsorption has become the most popular water treatment technology due to its convenient operation process, high treatment efficiency, and wide application range. Adsorbent is the most important factor that determines the treatment effect and cost of adsorption. The main adsorbents currently used are activated carbon and zeolite, but these adsorbents are relatively expensive. How to prepare low-cost and efficient adsorbents has become the focus of adsorption research. In recent years, there have been a lot of studies on the preparation of adsorbents using industrial solid waste as raw materials. As a byproduct of urban sewage treatment, residual sludge contains a large amount of organic matter such as benzene, polychlorinated biphenyls, chlorophenols, polychlorinated dibenzofurans, etc., as well as microorganisms such as parasites and pathogens. If not properly handled, it will cause great harm to the environment. Traditional sludge treatment and disposal methods including sanitary landfill and incineration can no longer meet the existing environmental requirements. Sludge resource utilization has become an inevitable choice to solve sludge treatment and disposal. Sludge contains a large amount of organic matter and a high carbon content. It is a good raw material for preparing biochar. However, sludge activated carbon also has some disadvantages, mainly including: (1) Poor pore structure: The pores of sludge activated carbon are poorly developed, which limits its adsorption capacity; (2) Limited adsorption capacity: Due to the limitations of the above structure and composition, the adsorption capacity of sludge activated carbon is not ideal. Therefore, it is of utmost importance to modify the sludge biochar to a certain extent and improve its adsorption effect. Summary of the invention

[0003] Technical problems to be solved: In view of the above technical problems, the purpose of the present invention is to provide a sludge carbon adsorption material and a preparation method thereof, which adopts the method of filling porous network particles inside the sludge carbon to form a regular porous structure; and the porous network particles present a very large specific surface area, which can increase the overall specific surface area of ​​the sludge carbon and improve the adsorption rate; at the same time, ZrV2O7 is coated on the porous network particles. ZrV2O7 is a negative thermal expansion material, which shrinks when heated and expands when cooled. In the preparation of the internal porous structure of the sludge carbon, it expands after cooling and can be more densely filled in the interior of the sludge carbon. At the same time, it can further combine with the sludge carbon to construct a C-ZrV2O7 structure, improve the stability of the internal porous structure of the sludge carbon, and utilize a stable and long-term adsorption effect. At the same time, after grinding, the coverage rate of ZrV2O7 is about 80%, and a porous structure is further formed on the surface of the porous mesh membrane to increase the specific surface area.

[0004] Technical solution: A sludge carbon adsorption material, wherein the sludge carbon adsorption material has porous network particles inside. Further, the porous network particles are spherical, with a particle size of 0.5-5 μm, a pore size of 2-23 nm, and a porosity of 80-97%. Further, the preparation method of the porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device to perform electrospinning to obtain a spinning membrane with a thickness of 10-20 μm; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1200-1400° C. at a heating rate of 2° C. for 2 hours, and then naturally cooled to room temperature. An annealing treatment is performed in an air atmosphere at 500° C. to obtain a porous mesh membrane; Step 5: Dissolve 7-10 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, and stir and dissolve at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 1-2 h, and dry at 60 °C; Step 7: Place in a muffle furnace and heat to 600°C at a rate of 5°C / min for 10-11h; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, and perform ultrasonic dispersion to form a suspension; Step 9: Place in a grinder and grind for 5-6 hours, take out, filter, wash and dry to obtain porous network particles. Furthermore, the electrospinning conditions in step 2 are: the spinning solution flow rate is 0.5-1.0 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 20-25°C, the inner diameter of the syringe needle is 0.24 mm, and the outer diameter is 0.45 mm. Furthermore, in step 5, the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1. Furthermore, in step 8, the mass ratio of the ZrV2O7 coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5. Furthermore, in step 9, the grinding conditions are: the rotation speed is 400 rpm, and the positive and negative rotations are alternated every 1 hour. The method for preparing the above-mentioned sludge carbon adsorption material comprises the following steps: (1) Take the dehydrated sludge and immerse it in a 30% phosphoric acid solution for 1-2 hours; (2) adding porous network particles, stirring evenly, and drying in an electric hot air drying oven at 80-100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 600-700° C. at a heating rate of 10° C. / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 30-60 min to obtain the sludge carbon adsorption material. Furthermore, the mass ratio of the dewatered sludge to the phosphoric acid solution is 1:1. Furthermore, the mass ratio of the dewatered sludge to the porous network particles is 100:(10-28). Beneficial effects: 1. The present invention adopts the method of filling the interior of the sludge carbon with porous network particles, which can solve the shortcomings of poor internal pore structure and underdeveloped pores of conventional sludge carbon and form a regular porous structure; and the porous network particles present a very large specific surface area, which can increase the overall specific surface area of ​​the sludge carbon and improve the adsorption rate. 2. The present invention adopts ZrV2O7 to coat the porous network particles. ZrV2O7 is a negative thermal expansion material, which shrinks when heated and expands when cooled. In the preparation of the internal porous structure of sludge carbon, it expands after cooling and can be more tightly filled in the interior of the sludge carbon. At the same time, it can further combine with the sludge carbon to construct a C-ZrV2O7 structure, improve the stability of the internal porous structure of the sludge carbon, and make use of a stable and long-term adsorption effect. At the same time, after grinding, the coverage rate of ZrV2O7 is about 80%, and a porous structure is further formed on the surface of the porous network membrane to increase the specific surface area. 3. The present invention uses phosphoric acid solution to etch channels inside the sludge carbon. On the one hand, it provides a large specific surface area and active groups for the sludge carbon. On the other hand, it can construct channels connecting the porous network particles, while also increasing the adsorption sites on the internal porous membrane and the ZrV2O7 surface, thereby improving the adsorption performance of the sludge carbon adsorption material. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic diagram of the structure of the sludge carbon adsorption material of the present invention. DETAILED DESCRIPTION The present invention proposes a sludge carbon adsorption material and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are: the spinning solution flow rate is 0.5 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: dissolving 9 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stirring and dissolving at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 2 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are as follows: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: dissolving 9 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stirring and dissolving at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 3 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are: the spinning solution flow rate is 1.0 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: dissolving 9 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stirring and dissolving at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 4 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 10 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: dissolving 9 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stirring and dissolving at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 5 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 20 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: dissolving 9 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stirring and dissolving at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 6 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are as follows: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: Dissolve 7 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stir and dissolve at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Example 7 The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are as follows: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: Dissolve 10 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, wherein the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:1, and stir and dissolve at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 2 h, and dry at 60 °C; Step 7: Place the mixture in a muffle furnace and heat it to 600°C at a rate of 5°C / min for 10 hours; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain ZrV2O7-coated particles, add isobutanol, ethanol and Tween 40, the mass ratio of ZrV2O7-coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 9: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. Comparative Example 1 The difference between this embodiment and Example 2 is that ZrV2O7 is not used for coating, as follows: The preparation method of porous network particles is as follows: Step 1: Take 5 g of polycarbosilane and 60 mL of tetrahydrofuran, stir to dissolve, add 5 g of polyvinyl pyrrolidone and 40 mL of ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device for electrospinning, the electrospinning conditions are as follows: the spinning solution flow rate is 0.8 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 21 ° C, the inner diameter of the syringe needle is 0.24 mm, the outer diameter is 0.45 mm, and a spinning membrane with a thickness of 15 μm is obtained; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. for 2 h, and then naturally cooled to room temperature. The porous mesh is annealed in an air atmosphere at 500° C. to obtain a porous mesh; Step 5: After cooling, take out, crush, pass through a 200-mesh sieve to obtain crushed particles, add isobutanol, ethanol and Tween 40, the mass ratio of crushed particles, isobutanol, ethanol and Tween 40 is 20:26:4:5, and ultrasonically disperse to form a suspension; Step 6: Place in a grinder and grind for 5.5 hours. The grinding conditions are: the rotation speed is 400 rpm, and the positive and reverse rotations are alternately rotated every 1 hour. Take out, filter, wash and dry to obtain spherical porous network particles with a particle size of 0.5-5 μm. The pore size, average porosity and ZrV2O7 coverage of the porous network particles of the above embodiment were measured, and the results are shown in Table 1 below: Table 1 After comprehensively evaluating the performance indicators of the above embodiments, embodiments 2 and 3 were selected for subsequent experiments. Example 8 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1 h; (2) adding 20 g of the porous network particles prepared in Example 2, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Example 9 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1.5 h; (2) adding 20 g of the porous network particles prepared in Example 2, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Example 10 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 2 h; (2) adding 20 g of the porous network particles prepared in Example 2, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Embodiment 11 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1.5 h; (2) adding 10 g of the porous network particles prepared in Example 2, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Example 12 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1.5 h; (2) adding 28 g of the porous network particles prepared in Example 2, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Embodiment 13 A method for preparing a sludge carbon adsorption material comprises the following steps: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1.5 h; (2) adding 20 g of the porous network particles prepared in Example 3, stirring evenly, and drying in an electric hot air drying oven at 100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. Comparative Example 2 The difference between this embodiment and embodiment 9 is that the spherical porous network particles prepared in comparative example 1 are used to replace the porous network particles prepared in embodiment 2, and other conditions remain unchanged. Comparative Example 3 This example is a conventional sludge carbon adsorption material, and the specific preparation method is as follows: (1) Take 100 g of dehydrated sludge and immerse it in 100 g of 30% phosphoric acid solution for 1.5 h; (2) drying in an electric hot air drying oven at 100°C for 24 hours and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 650°C at a heating rate of 10°C / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 50 min to obtain the sludge carbon adsorption material. The specific surface area of ​​each embodiment was measured using a fully automatic specific surface area analyzer; Determination of Cd in water in each embodiment 2+ and Pb 2+ The adsorption amount is shown in Table 2 below: Table 2

Claims

1. A sludge carbon adsorption material, characterized in that: The sludge carbon adsorption material has porous network particles inside.

2. A sludge carbon adsorption material according to claim 1, characterized in that: The porous network particles are spherical, with a particle size of 0.5-5 μm, a pore size of 2-23 nm, and a porosity of 80-97%.

3. The sludge carbon adsorption material according to claim 1, characterized in that: The preparation method of the porous network particles is as follows: Step 1: Take 5 g polycarbosilane and 60 mL tetrahydrofuran, stir to dissolve, add 5 g polyvinyl pyrrolidone and 40 mL ethanol, and continue stirring for 12 h as the electrospinning solution; Step 2: placing the electrospinning solution in a syringe in an electrospinning device to perform electrospinning to obtain a spinning membrane with a thickness of 10-20 μm; Step 3: placing the spun membrane in a box furnace for pre-oxidation at 200°C for 2h; Step 4: In an argon atmosphere, the temperature is raised to 1200-1400° C. at a heating rate of 2° C. for 2 hours, and then naturally cooled to room temperature, and annealed in an air atmosphere at 500° C. to obtain a porous mesh membrane; Step 5: Dissolve 7-10 g of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide in 100 mL of deionized water, and stir and dissolve at 70° C. to obtain a ZVO precursor solution; Step 6: Disperse 4 g of porous mesh in 200 mL of ethanol, add 10 mL of ZVO precursor solution, stir for 1-2 h, and dry at 60 °C; Step 7: Place in a muffle furnace and heat to 600°C at a rate of 5°C / min for 10-11h; Step 8: After cooling, take out, crush, and pass through a 200-mesh sieve to obtain particles coated with ZrV2O7, add isobutanol, ethanol and Tween 40, and perform ultrasonic dispersion to form a suspension; Step 9: Place in a grinder and grind for 5-6 hours, take out, filter, wash and dry to obtain porous network particles.

4. A sludge carbon adsorption material according to claim 3, characterized in that: The electrospinning conditions in step 2 are as follows: the spinning solution flow rate is 0.5-1.0 mL / h, the spinning voltage is 18 kV, the distance from the receiving plate is 15 cm, the spinning temperature is 20-25° C., the inner diameter of the syringe needle is 0.24 mm, and the outer diameter is 0.45 mm.

5. The sludge carbon adsorption material according to claim 3, characterized in that: In step 5, the molar ratio of citric acid, zirconium nitrate pentahydrate and vanadium pentoxide is 3:1:

1.

6. The sludge carbon adsorption material according to claim 3, characterized in that: In step 8, the mass ratio of the ZrV2O7 coated particles, isobutanol, ethanol and Tween 40 is 20:26:4:

5.

7. The sludge carbon adsorption material according to claim 3, characterized in that: The grinding conditions in step 9 are: the rotation speed is 400 rpm, and the positive and negative rotations are alternated every 1 hour.

8. The method for preparing a sludge carbon adsorption material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Take the dehydrated sludge and immerse it in a 30% phosphoric acid solution for 1-2 hours; (2) adding porous network particles, stirring evenly, and drying in an electric hot air drying oven at 80-100° C. for 24 h, and crushing to a particle size of 100-150 μm; (3) placing the sludge in a tubular pyrolysis furnace, heating the temperature to 600-700° C. at a heating rate of 10° C. / min under the protection of a nitrogen atmosphere, and pyrolyzing the sludge for 30-60 min to obtain the sludge carbon adsorption material.

9. The method for preparing a sludge carbon adsorption material according to claim 8, characterized in that: The mass ratio of the dewatered sludge to the phosphoric acid solution is 1:

1.

10. The method for preparing a sludge carbon adsorption material according to claim 8, characterized in that: The mass ratio of the dewatered sludge to the porous network particles is 100:(10-28).